The evolution of corporate culture in the social and economic transformation - Orlova, Lyudmila Viktorovna; Natalia Nikolaevna Pronina, Galina Pavlovna Gagarinskaya, Elena Vladimirovna Muller,; Nozdrina, Ekaterina Olegovna (Opción, 2019)
The aim of the study is to investigate the evolution of corporate culture in the process of social and economic transformation of modern Russian business organization. The results of the research aimed at identifying the main motivating and limiting factors of employees at the Russian enterprise Electroshield Samara in the organization of  labor. Based on sociological research methods, such as observation, survey, questionnaire, and focus groups, the manuscript presents conclusions about the competent use of corporate culture mechanisms in order to increase staff motivation in work processes.